The sovereign debt crisis: placing a curb on growth - Brender, Anton; Pisani, Florence; Gagna, Emile (Brussels, 2013)
"This book provides an update to the major 2012 study by the same authors on the dual role of the public sector as the provider of the ultimate riskless asset and, at the same time, the source of a potential major systemic risk. In this second edition, Brender and his colleagues concentrate again on the tension between the need for the public sector to sustain demand in the face of a deleveraging private sector and the longer-term challenges of sustainability for fiscal policy in the major developed economies of the US, Japan and the euro area. In short, their principal thesis is that sovereign debt is in crisis.  This crisis is apparent in the euro area, but it is also real, if at present only latent, in the US and Japan. The book shows how this process has evolved in these three big developed economies – and how their policy choices impact on global financial markets."